The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.34172/ipp.2020.25
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum ferritin levels in pregnant women with preterm and term deliveries

Abstract: Introduction: Despite high rates of mortality and morbidity due to preterm delivery, none of the diagnostic and biochemical tests could help to accurately identify the cases at risk of preterm delivery. Objectives: Since ferritin is an acute phase reactant, this study aimed to evaluate serum ferritin levels in women with preterm and term delivery. Methods: This study was conducted on 150 women with preterm delivery (50 cases in each of the groups 24-30, 30-34, and 34-37 weeks of pregnancy), 150 women with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, ferritin level was significantly elevated in pre-term births than in term births in cases with PROM or an extended leakage (p value<0.001). In addition to our results, Jahedbozorgan et al, [11] demonstrated that in pre-term births, ferritin level was significantly elevated in patients with PROM or with an extended leakages (>12 h). Furthermore, in cases with PROM or extended leakages, ferritin level was significantly elevated in pre-term than in term births.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, ferritin level was significantly elevated in pre-term births than in term births in cases with PROM or an extended leakage (p value<0.001). In addition to our results, Jahedbozorgan et al, [11] demonstrated that in pre-term births, ferritin level was significantly elevated in patients with PROM or with an extended leakages (>12 h). Furthermore, in cases with PROM or extended leakages, ferritin level was significantly elevated in pre-term than in term births.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the best cutoff of ferritin levels for pre-term birth in PROMs and an extended leakages was 44.5 ng/mL and 45 ng/mL, resp. Also, Jahedbozorgan et al, [11] found that ferritin levels of 37.5 ng/mL known as the optimum cutoff for pre-term birth, in comparison to the in term birth, and its sense, spec., and accuracy were 78.70%, 68.70%, and 73.60%, resp. When comparing our results regarding roc curve for s-ferritin, Abdel-Malek et al, [7] revealed the cutoff point of s-ferritin amid the both groups was 31 ng/ml with sense 92.80%, spec.…”
Section: Discussionmentioning
confidence: 99%
“…Erdinc et al also published similar results of serum ferritin levels being associated with PTB (44). A study by Tayebeh et al which excluded cases of anemia showed similar results with serum ferritin >37.5 ng/ml with a sensitivity of 78.7 % and specificity of 68.7% could indicate preterm delivery (45).…”
Section: E) Serum Ferritinmentioning
confidence: 68%
“…Ferritin is the main intracellular storage protein that retains iron in an insoluble and non-toxic state, which is reported to increase in some acute phase reactions such as inflammation. 14 Subclinical infections in pregnant women can increase ferritin levels as an acute phase reactant and cause spontaneous rupture of the membranes. 15 Uterine inertia occurs due to the inability of the uterus to contract due to myometrial fiber dysfunction, an effect of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%